Pengaruh Brand Awareness, Persepsi Konsumen dan Kualitas Produk terhadap Keputusan Pembelian Produk Wedrink di Kota Batam - Sinaga, Ledyana Nitami; Wasiman, Wasiman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Wedrink, a rapidly expanding beverage brand originating from China, has gained popularity in Batam, Indonesia. In a highly competitive market, understanding consumer behavior is essential for maintaining business sustainability. This study aims to examine the influence of brand awareness, consumer perception, and product quality on purchase decisions of Wedrink products in Batam. A quantitative descriptive approach was employed, with data collected through an online questionnaire distributed to 384 respondents using accidental sampling. The data were analyzed using SPSS version 26, incorporating validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and multiple linear regression analysis. The results reveal that brand awareness, consumer perception, and product quality each have a significant and positive impact on purchase decisions. The model demonstrates a strong explanatory power with an adjusted R² of 45.0%, while the F-test confirms the joint significance of the independent variables (p < 0.001). These findings highlight the importance of building brand familiarity, delivering consistent product quality, and aligning offerings with consumer expectations to strengthen purchasing behavior in the beverage industry.